Atripla™ – HIV therapy in one pill - Boris Julg; Johannes R Bogner (Dove Medical Press, 2008)
Boris Julg, Johannes R BognerMedizinische Poliklinik, Department of Infectious Diseases, University of Munich Medical School, Downtown Campus, GermanyAbstract: In July 2006 Atripla™ was approved by the US Food and Drug Administration (FDA), combining the active ingredients of one NNRTI and two NRTIs. Atripla™ is the first “one-pill-daily” regimen licensed for the treatment of HIV-1 infection in patients older than 18 years. Atripla™ contains efavirenz 600 mg, emtricitabine 200 mg and tenofovir disoproxil fumarate 300 mg. It therefore combines 3 compounds which have been widely used before and which were recommended for initial therapy due to their potency, tolerability, and safety profile. Efficacy and safety data of efavirenz, tenofovir DF, and emtricitabine are reviewed compared with other antiretroviral drugs, which are used as initial therapy for treatment-naive patient.Keywords: Atripla™antiretroviral therapy, new “one-pill-daily” regimen, review efficacy and safety data